2017
DOI: 10.18203/2320-1770.ijrcog20175002
|View full text |Cite
|
Sign up to set email alerts
|

Partograph versus no partograph: effect on labour progress and delivery outcome: a comparative study

Abstract: Background: Abnormal labour which includes prolonged labour and obstructed labour remain major causes of maternal morbidity. The major reason for neonatal mortality, birth asphyxia and subsequent morbidity is essentially the repercussion which occurs when a complicated labour is not intervened at the right time. A Partograph provides a graphic overview of the progress of labour and records information about maternal and fetal condition during labour. It is considered to be a very effective tool to monitor labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 3 publications
4
11
0
Order By: Relevance
“…7 Stduy conducted by Ahmed B et al concluded that the duration of first stage and second stage of labour was significantly decreased in the group where partograph was used. 8 Similar findings have been reported in other study too. 9 In present study, rate of NICU admission and its indications were studied in both cases and control.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…7 Stduy conducted by Ahmed B et al concluded that the duration of first stage and second stage of labour was significantly decreased in the group where partograph was used. 8 Similar findings have been reported in other study too. 9 In present study, rate of NICU admission and its indications were studied in both cases and control.…”
Section: Discussionsupporting
confidence: 86%
“…7 In the study by Ahmed B et al, there were 91% normal vaginal deliveries in partograph group and 81.5% in other non partograph group. 8 Considering prolonged labour, it was significantly reduced in the group where partograph was used as compared to other group. Around 7.3% of control group had prolonged labour of more than 16 hours in present study while none of the case had such prolong labour.…”
Section: Discussionmentioning
confidence: 97%
“…Even in uncomplicated pregnancies there is increased risk in stillbirth associated with maternal age. In older mothers, stillbirth rate increases as the gestational age increases beyond 37 weeks [26].…”
Section: Discussionmentioning
confidence: 99%
“…Participants who were not served using partograph were in higher odds of facing stillbirth than their counter parts. Poor partograph utilization may resulted in prolonging second stage of labor which could also resulted in depriving interventions like; cesarean section, augmentation and instrumental delivery [2628].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this tool is to alert midwives to abnormalities in maternal or fetal well-being and progress of labour [5]. Moreover, it is a useful tool to prevent prolonged and obstructed labour [6,7]. Even though Cochrane review was not certain on the effect of routine use of partograph to monitor labour [5], the multi-center trial in South East Asia showed a significant reduction in intra-partum still birth, prolonged labour, augmentation, emergency caesarean section and vaginal examination [8].…”
Section: Introductionmentioning
confidence: 99%